DAMPAK BUDIDAYA PERTANIAN INTENSIF TERHADAP KUALITAS AIR PERMUKAAN DESA KANIGORO KECAMATAN NGABLAK KABUPATEN MAGELANG - Komarawidjaja, Wage (Jurnal Teknologi Lingkungan, 2011)
Kanigoro at Ngablak Sub-District in Magelang is one of the Villages which is topographically lower than the adjacent village in the same sub-district. The main activity of village inhabitant is farmer in intensive agriculture that is indicated by a lot of fertilizer and pesticide utilization. Therefore, the exceeding dosage of fertilizer and pesticide in plant cultivation could become an anxious environmental problem due to the high concentration of them in springs water that they called as Tuk and river water more than the quality standard of National regulation. Based on Data analysis, it can be concluded that laboratory analysis result of water quality in the village Kanigoro, generally still meet the quality standard. This is showed by the concentration of heavy metals (As, Cu, Cd, Hg, Zn and Fe) and pesticides (Aldrin, BHC, Chlordane, DDT, Dieldrin, Endrin, Heptachlor,Heptachlo epoxide, Lindane, Methoxychlor and Toxaphene), except for some points sampling contain heavy metals plumbum (Pb) exceeded water quality standard of the Minister of Health (Depkes) and Government Regulation ClassÃ‚Â I (raw water) of PP 82/2001. While the density of microbial total coliform and E. coli detected abundant compare to the water quality standard of the Minister of Health, particularly for the use of water as raw water or clean water. However, it is possible to utilize water directly for agriculture and fish farming activities and the use for drinking water after cooked first